Diagnostic of the use of fire in agricultural activities at the Estancia Vieja site, Portoviejo canton, Manabí, Ecuador - Quijije Briones, Vielka Monserrate (2025)
The use of fire by farmers has been a common practice worldwide for decades. The objective of this work was to diagnose the use of fire in agricultural activities at the Estancia Vieja site, Portoviejo canton, Manabí, Ecuador. For the development of the research, a non-experimental, descriptive, cross-sectional design was used. The sample size was calculated with the Decision Analyst STATSTM 2.0 software. The information was obtained by applying a semi-structured questionnaire to 123 agricultural producers. The statistical analysis was performed with the SPSS program (Version 22.0). The hot spots for contrast with the months in which fire is most used were obtained from the Fire Information for Resource Management System. In the locality, the use of fire in agricultural activities is common, mainly for clearing land destined for the implementation of agricultural crops. The respondents showed that they have knowledge about the hours and months in which they should burn in order to achieve the objective of eliminating the greatest amount of crop residues and weeds, as well as about the way to burn these fuels depending on the existing quantity of them and about the prevention measures they observe before burning. This information supports decision-making in the field of integrated fire management. It is suggested that similar research be carried out in other localities but considering the relationship of the use of fire with meteorological conditions, fire behavior and its effects on the environment.